Neural Representation of Motor Output, Context and Behavioral Adaptation in Rat Medial Prefrontal Cortex During Learned Behavior - de Haan, Roel; Lim, Judith; van der Burg, Sven A.; Pieneman, Anton W.; Nigade, Vinod; Mansvelder, Huibert D.; de Kock, Christiaan P. J. (Frontiers in Neural Circuits, 2018)
Selecting behavioral outputs in a dynamic environment is the outcome of integrating multiple information streams and weighing possible action outcomes with their value. Integration depends on the medial prefrontal cortex (mPFC), but how mPFC neurons encode information necessary for appropriate behavioral adaptation is poorly understood. To identify spiking patterns of mPFC during learned behavior, we extracellularly recorded neuronal action potential firing in the mPFC of rats performing a whisker-based ‘Go’/’No-go’ object localization task. First, we identify three functional groups of neurons, which show different degrees of spiking modulation during task performance. One group increased spiking activity during correct ‘Go’ behavior (positively modulated), the second group decreased spiking (negatively modulated) and one group did not change spiking. Second, the relative change in spiking was context-dependent and largest when motor output had contextual value. Third, the negatively modulated population spiked more when rats updated behavior following an error compared to trials without integration of error information. Finally, insufficient spiking in the positively modulated population predicted erroneous behavior under dynamic ‘No-go’ conditions. Thus, mPFC neuronal populations with opposite spike modulation characteristics differentially encoded context and behavioral updating and enable flexible integration of error corrections in future actions.